Pembebasan Perempuan Qasim Amin: Telaah Kritis Pemikirannya Terhadap Hijab: Pembebasan Perempuan menurut Qasim Amin: Telaah Kritis Pemikirannya terhadap Hijab - Royyan Bachtiar (Journal of Islamic and Occidental Studies, 2023)
This article discusses Qosim Amin's thoughts on the hijab within the context of Islamic Sharia. Qosim Amin was a Muslim thinker who actively advocated for the liberation of women in the Islamic world. One of his main ideas pertains to the Sharia requirement of the hijab, which he believed needed to be reconsidered. According to him, the hijab is not a religious obligation but merely a matter of tradition or culture. Furthermore, he viewed the obligation of the hijab as restricting women's freedom, thereby hindering societal progress. Using a critical analysis method, this research shows that Qosim Amin's perspective on the hijab contradicts the understanding of Islamic Sharia by scholars. The majority of scholars agree that the hijab is a religious obligation stated in the Qur'an and Sunnah, rather than a mere cultural tradition. Additionally, his notion that the hijab symbolizes the restriction of women is also incorrect. A devout Muslim woman who adheres to Islamic Sharia will wear the hijab to uphold her honor and sense of modesty. The implication of this research is the importance of understanding the hijab as an integral part of Islamic Sharia and not merely a symbol of women's restrictions.